Effect of Company Age, Size of Public Accounting Firm and Firm Solvency on Audit Delay - Oktariansyah Oktariansyah; Andri Eko Putra; Henny Karunia Putri (Jurnal Akuntansi, 2022)
This research aims to determine the impact of firm age, Size of Public Accounting Firm (PAF size), and firm solvency on audit delay. The population in this study is the financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) audited for the 2017-2019 period. The study incorporated a quantitative research design. The samples used in this study were 32 companies with four years of observation, so a sample of 96 was obtained using the purposive sampling method. The data analysis technique used is multiple linear regression through SPSS version 21. Audit Delay is affected by Company Age, Audit Delay is affected by the PAF Size, Audit Delay is not affected by Company Solvency, and There is an effect of Company Age, size of the Public Accounting Firm and firm solvency on Audit Delay